2009
DOI: 10.1038/jcbfm.2009.219
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Neural Precursor Cells in Matrigel Scaffolding Improves Outcome from Focal Cerebral Ischemia after Delayed Postischemic Treatment in Rats

Abstract: Transplantation of neural cells is a potential approach for the treatment of stroke, but the disruption of tissue architecture that accompanies stroke may limit the efficacy of transplantation. One strategy for enhancing the ability of transplants to restore brain structure and, thereby, function is to administer cells together with biomaterial scaffolding. We occluded the middle cerebral artery in adult rats and, 3 wks later, injected one of the following into the infarct cavity: (a) artificial cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 44 publications
2
136
0
3
Order By: Relevance
“…These data now provide an impetus and opportunity to determine the extended utility of LIF signaling on NP cells to be used in neural cell-based therapies. Although others have used the NP cells we previously generated in animal models, the effect of LIF on these NP cells in vivo was not investigated [5]. Here both LIF À and LIF þ treated cells equally reduce infarct volumes in mouse models of stroke in as little as 24 hours postinjection (Fig.…”
Section: Lif Pretreatment Of Np Cells In Stroke Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…These data now provide an impetus and opportunity to determine the extended utility of LIF signaling on NP cells to be used in neural cell-based therapies. Although others have used the NP cells we previously generated in animal models, the effect of LIF on these NP cells in vivo was not investigated [5]. Here both LIF À and LIF þ treated cells equally reduce infarct volumes in mouse models of stroke in as little as 24 hours postinjection (Fig.…”
Section: Lif Pretreatment Of Np Cells In Stroke Modelmentioning
confidence: 99%
“…We have previously derived a self-renewing but fate-restricted neural progenitor (NP) cell line from hESC that can generate highly enriched neuronal populations under specific conditions [2,3], thus serving as a potentially unlimited source of human neurons for both basic [4] and applied research [5]. This progenitor line has previously been used to study neurotoxicity, differentiation to specific neuronal phenotypes, drug screening, and transplantation experiments in rodent models of stroke [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because brain tissue architecture is disrupted in the ischemic brain, the use of biodegradable scaffolds may help transplanted stem cells regenerate and/or restore damaged brain structures and functions, by affecting cell differentiation, morphology, adhesion, or gene expression (Kleinman & Martin, 2005;Steindler, 2002). Jin et al showed that transplantation of human neural precursor cells (NPCs) in Matrigel scaffolding at the time of transplantation partially improved therapeutic outcome compared to that of NPCs without Matrigel scaffolding, and that the use of NPC/Matrigel cultures dramatically improved the therapeutic effect (Jin et al, 2010). These reports indicate that, when using transplantation methods employing pre-treatment with GDNF, or Matrigel scaffolding, cytoprotective effects that enhance the survival rate of stem cells require time to develop in vitro before transplantation and that such development might be related to the enhanced cytoprotective effects observed after transplantation.…”
Section: Graft Survivalmentioning
confidence: 99%
“…In an attempt to improve transplant survival and behavioral outcome, Jin et al found that intralesional transplantation of nestin/Sox2-immunopositive neuronal precursor cells (NPCs) derived from BG01 human embryonic stem cells 3 weeks after distal MCAO in rats reduced infarct volume and improved behavioral outcome 4-9 weeks post-transplant (Jin et al, 2010a). In another study, they found that the beneficial effects of transplantation occurred in both young adult (3-month-old) and aged (24-month-old) rats (Jin et al, 2010b).…”
Section: From Theory To Practice: Nscs Transplant In Rodent Models Ofmentioning
confidence: 99%